2020
DOI: 10.5603/gp.a2020.0122
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anti-müllerian Hormone (AMH) and Hormonal Assays for Phenotypic Classification of Polycystic Ovary Syndrome

Abstract: Objectives:The aim is to compare the hormonal status and anti-müllerian hormone (AMH) levels of patients who have different polycystic ovary syndrome (PCOS) phenotypes, polycystic ovarian morphology (PCOM) and healthy women. Material and methods:A total of 350 PCOS women, 71 women with PCOM and 79 healthy women with normal ovarian morphology (NOM) were observed. PCOS patients were divided into groups according to the phenotypes. Phenotype A-characterized by anovulation, hyperandrogenism and PCOM; phenotype B-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In the present study, it was observed that AMH levels were significantly higher in phenotype A (9.25 ± 4.98 ng/mL) compared to other phenotypes within the RC-PCOS group, while phenotype B exhibited the lowest AMH level (6.88 ± 3.88 ng/mL), potentially indicating the presence of OA and PCOM. These findings are consistent with previous research that suggests AMH serves as a marker of PCOS severity [32,33].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, it was observed that AMH levels were significantly higher in phenotype A (9.25 ± 4.98 ng/mL) compared to other phenotypes within the RC-PCOS group, while phenotype B exhibited the lowest AMH level (6.88 ± 3.88 ng/mL), potentially indicating the presence of OA and PCOM. These findings are consistent with previous research that suggests AMH serves as a marker of PCOS severity [32,33].…”
Section: Discussionsupporting
confidence: 93%
“…Hyperandrogenism was included in all of these diagnostic criteria, except for PCOS patients with phenotype D, which is within the Rotterdam criteria and accompanied by oligo‐anovulation and polycystic ovaries 2 . In addition to hyperandrogenism, luteinizing hormone (LH) hypersecretion and increased LH/follicle‐stimulating hormone ratio have also been demonstrated in patients with PCOS 6,7 . Increased LH secretion is seen as one of the causes of hyperandrogenism in PCOS and hyperandrogenism is one of the most important factors that is involved in the pathogenesis of this syndrome 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to hyperandrogenism, luteinizing hormone (LH) hypersecretion and increased LH/follicle‐stimulating hormone ratio have also been demonstrated in patients with PCOS 6,7 . Increased LH secretion is seen as one of the causes of hyperandrogenism in PCOS and hyperandrogenism is one of the most important factors that is involved in the pathogenesis of this syndrome 7 . Hyperandrogenism is seen in approximately 60% of patients with PCOS and is one of the responsible factors for symptoms and findings such as anovulation, subfertility, acne, and hirsutism in these patients 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation